Lund–Mackay and modified Lund–Mackay score for sinus surgery in children with cystic fibrosis. Issue 8 (August 2015) - Do, Bao Anh; Lands, Larry C.; Mascarella, Marco A.; Fanous, Amanda; Saint-Martin, Christine; Manoukian, John J.; Nguyen, Lily H.P.
Abstract Objective Patients with cystic fibrosis (CF) frequently present with severe sinonasal disease often requiring radiologic imaging and surgical intervention. Few studies have focused on the relationship between radiologic scoring systems and the need for sinus surgery in this population. The objective of this study is to evaluate the Lund–Mackay (LM) and modified Lund–Mackay (m-LM) scoring systems in predicting the need for sinus surgery or revision surgery in patients with CF. Methods We performed a retrospective chart review of CF patients undergoing computed tomography (CT) sinus imaging at a tertiary care pediatric hospital from 1995 to 2008. Patient scans were scored using both the LM and m-LM systems and compared to the rate of sinus surgery or revision surgery. Receiver–operator characteristics curves (ROC) were used to analyze the radiological scoring systems. Results A total of 41 children with CF were included in the study. The mean LM score for patients undergoing surgery was 17.3 (±3.1) compared to 11.5 (±6.2) for those treated medically (p < 0.01). For the m-LM, the mean score of patients undergoing surgery was 20.3 (±3.5) and 13.5 (±7.3) for those medically treated (p < 0.01). Using a ROC curve with a threshold score of 13 for the LM, the sensitivity was 89.3% (95% CI of 72–98) and specificity of 69.2% (95% CI of 39–91). At an optimal score of 19, the m-LM system produced a sensitivity of 67.7% (95% CI of 48–84) and specificity of 84.6% (95% CI of 55–98). Conclusion The modified Lund–Mackay score provides a high specificity while the Lund–Mackay score a high sensitivity for CF patients who required sinus surgery. The combination of both radiologic scoring systems can potentially predict the need for surgery in this population.